Analisis Pengaruh Lokasi, Produk, Citra Merek dan Promosi Terhadap Keputusan Pembelian Mobil Suzuki (Studi Kasus di PT Gedong Jembar Pemalang) - Hartoyo Hartoyo; Santi Suciningtyas (Universitas Peradaban, 2016)
This research entitle the “ Analysis of influence location, product, brand image, and promotion to purchase decision Suzuki car” (Case Study in PT. Gedong Jembar Pemalang)”. This research target is : first, to know and analyse influence of location variable to purchase decision Suzuki car variable, second, to know and analyse influence of product variable to purchase decision Suzuki car variable, third, to know and analyse influence of brand image variable to purchase decision Suzuki car variable, fourth, to know and analyse influence of promotion variable to purchase decision Suzuki car variable, fifth, to know and analyse influence of location variable, product variable, brand image variable, and promotion variable to purchase decision Suzuki car variable. At this research used by sample as much 90 respondents that is some of customer PT. Gedong Jembar Pemalang. As for examination of at this research done with validity test, reliability, classical assumptions, multiple linear regression analysis and hypothesis test in the form of t test and F test. With multiple linear regression analysis at this research obtained by result b1 = 0,237 showing influence which are significance of location variable (X1) equal 0,237 to purchase decision Suzuki car, b2 = 0,188 showing influence which are significance of product variable (X2) equal 0,188 to purchase decision Suzuki car, b3 = 0,177 showing influence which are significance of brand image variable (X3) equal 0,177 to purchase decision Suzuki car, b4 = 0,441 showing influence which are significance of promotion variable (X4) equal 0,441 to purchase decision Suzuki car. While for the hypothesis examination in partial used by t test, obtained by value tcount for location variable (X1) equal to 3,080, product variable (X2) equal to 3,059, brand image variable (X3) equal to 2,716, promotion variable (X4) equal to 2,716 with criterion of ttables of equal to 1,987 used in this examination. And for examination as a whole be used by F test. Be obtained by F count equal to 32,641 with level significance of 0,000 far smaller than 0,05 and bigger than Ftable of equal to 2,48. Coefficient determinant (R2) equal to 60,6%, what mean that purchase decision Suzuki car together be influenced by location variable, product variable, brand image variable, and promotion variable, while the remaining equal to 39,3% influenced by other variables that are not included in the model equations.